Mercury pollution a transdisciplinary treatment - Zuber, Sharon L.; Newman, Michael C. (CRC Press, 2012)
"Using mercury pollution as an example, this book illustrates the interdisciplinary approach required for solving environmental problems. It explains the details of the natural cycling of mercury in and on the earth and discusses how humans have dramatically disrupted its exchange among the earths soil, air, and water. The chapters discuss history, media, and politics in relation to mercury and contain links to established websites with specific resources for readers. Also included are smaller case studies, such as the Minamata tragedy, fish consumption, and international treaties"--